Differential ultrastructural aberrations of collagen fibrils in Ehlers-Danlos syndrome types I-IV as a means of diagnostics and classification - Haußer-Siller, Ingrid; Anton-Lamprecht, Ingrun (Human genetics, 1994)
Among the different subtypes of Ehlers-Danlos syndrome (EDS), the dominant types I-III have, so far, been uninformative biochemically and molecular genetically, and diagnostic problems with subgroup boundaries often arise. We have investigated the ultrastructural pattern of connective tissue macromolecules in skin biopsy specimens of some 85 patients aged 4 months-54 years who exhibit clinical symptoms or the suspicion of EDS I-IV. Based on the differential features of collagen fibrils and ground substance material, four distinct groups could be established. Group I (clinically EDS type I) showed disorganized collagen bundles and dense aggregations of collagen fibrils with bizarre shapes. Group II (clinically varying from EDS types I-III) revealed collagen bundles that regularly contained numerous “composite collagen fibrils” with enlarged “flower-like” cross-sections and rope-like longitudinal sections, often associated with increased amounts of matrix substances in the form of electron-dense irregular strands and filaments in a branched network. Group III (clinically EDS types II-III) presented smaller isolated collagen flowers and ropes associated with excessive filamentous ground substance material and flocculent material. Group IV (with clinical symptoms of EDS type IV) had a dermis thinned to one third of the normal and a reduced number of collagen bundles with small diameter fibrils. In 13 patients, the abnormal ultrastructural dermal architecture did not coincide with any of these four groups or with the pattern of any other inherited connective tissue disorder. In 16 additional patients with mostly mild clinical symptoms, such as muscle weakness and small joint hyperlaxity, no ultrastructural aberrations could be found. Even though the primary defects underlying the respective aberration of the collagen fibrils are still unknown, the differential ultrastructural changes of the collagen fibrils together with clinical symptoms should, as in other heterogeneous genetic disorders, facilitate the (provisional?) classification of EDS and permit the diagnosis of individual cases.